Biodegradable copolyester/starch blends - preparation, mechanical properties, wettability, biodegradation course - Turečková, J.; Prokopová, I.; Niklová, P.; Šimek, J.; Šmejkalová, P.; Keclík, F. (Polimery, 2022)
A set of blends of an aromatic-aliphatic copolyester containing 35 mol. % of aromatic ester units and plasticized wheat starch has been prepared. The copolyester used in this process was synthesized by polycondensation of the product of solvolysis of polyethyleneterephthalate (PET) from disposed beverage bottles by an aqueous solution of lactic acid. The blends copolyester/starch were characterized by their tensile strength and wetting behavior. Biodegradability of the blends was tested by using of mixed culture of microorganisms of digested sludge from wastewater treatment plant under anaerobic thermophilic conditions (55°C).